PERAN BP2D PROVINSI JAWA BARAT DALAM PENYUSUNAN REKOMENDASI KEBIJAKAN BERBASIS BUKTI PEMBERDAYAAN LANSIA TAHUN 2025 - Rebeca Yufiar Agustin; Novie Indrawati Sagita; Agus Taryana (LPPM Universitas Abdurrab, 2026)
The increasing number of elderly people in West Java Province necessitates public policies that are responsive, integrated, and evidence-based. However, the practice of evidence-based policymaking at the local government level still faces significant challenges, particularly weak data coordination among regional government agencies involved in elderly empowerment issues. This study aims to analyze the role and coordination strategies of the Regional Research and Development Agency (BP2D) of West Java Province in addressing these challenges through the facilitation of the West Java Research Forum (WJRF), to identify factors contributing to suboptimal data coordination, and to formulate efforts to strengthen cross-sectoral data-sharing systems. The authors argue that BP2D plays not only a role as a producer of policy recommendations but also as a facilitator and catalyst for institutional collaboration in the evidence-based policymaking process. This study employs a descriptive qualitative method, with data collected through interviews, observations, documentation, and literature review. The findings indicate that BP2D has established a collaborative dialogue space through the WJRF; however, the resulting data coordination remains non-binding due to fragmented authority, the absence of operational regulations, and sectoral budgeting and accountability systems. Therefore, strengthening supporting regulations, integrating inter-agency data systems, and creating institutional incentives are key to enhancing the effectiveness of evidence-based elderly empowerment policy formulation and implementation in West Java.